Teori dan Prosedur Studi Kasus: Rijal al-Hadits Tentang Analisis Kritis Hadits - Fahmi Royhan; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research is motivated by the fact that, in many cases, the assessment of a narrator is not always based on objective evidence, but also involves subjective interpretations by scholars. This raises questions about the standards of objectivity in the science of Rijal al-Hadith and to what extent subjectivity plays a role in evaluating narrators. The aim of this study is to explore and critically analyze the methodology used in Rijal al-Hadith. The research applies a descriptive-analytical approach, with data collected through literature study techniques. The data is then analyzed using qualitative data analysis techniques. The results of this study indicate the presence of subjectivity and complexity, especially related to differences in scholarly views on the credibility of narrators such as Al-Waqidi, which highlights the need for contextual understanding and variation in interpretation. Furthermore, Rijal al-Hadith also faces challenges in the context of modernity and social complexity, requiring an evaluation and updating of methodologies to make them more inclusive. The findings of this research imply the necessity of a holistic approach that considers social, cultural, and intellectual aspects, as well as the use of digital technology and interdisciplinary approaches to enhance the accuracy of narrator assessments.